2020
DOI: 10.5552/drvind.2020.1957
|View full text |Cite
|
Sign up to set email alerts
|

Durability and Mechanical Performance of Differently Treated Glulam Beams during Two Years of Outdoor Exposure

Abstract: The performance of the composites is influenced by the service life of input raw wood material and used adhesives. The aim of the study was to assess the durability and mechanical performance of glulam beams treated in a different way (thermally modified and/or treated with copper-based wood preservative) and exposed in an outdoor application. Glulam beams (83 mm × 68 mm × 1100 mm), made of three layers of Norway spruce (Picea abies) with PUR adhesives used have been exposed in use class 3.2 in a horizontal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…They discovered that the results were good. The mechanical characteristics of three-layer glulam beams (83 × 68 × 1100 mm) manufactured of Norway spruce were examined by Kržišnik et al (2020). Research has indicated that in the case of untreated samples, after two years of exposure to the outdoors, some faint indications of fungal decomposition were seen.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that the results were good. The mechanical characteristics of three-layer glulam beams (83 × 68 × 1100 mm) manufactured of Norway spruce were examined by Kržišnik et al (2020). Research has indicated that in the case of untreated samples, after two years of exposure to the outdoors, some faint indications of fungal decomposition were seen.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, non-biocidal solutions are preferred, and various biocide-free modifications are available on an industrial scale [10]. One well-established technique is thermal modification or heat treatment [11]. According to data from [13], Europe produces up to 530,000 m 3 of heattreated (HT) wood annually.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ansell [17], at the beginning wood-based composites were predominantly used for indoor applications; however, nowadays they are frequently seen in outdoor applications exposed to changing weather conditions as well [18]. In addition to changing ambient humidity, GLT stored outdoors is also susceptible to weathering process and degradation by fungi, which can significantly affect the mechanical characteristics of structural beams [19][20][21].…”
Section: Introductionmentioning
confidence: 99%